Tetracationic fluorinated zinc(ii)phthalocyanine: Synthesis, characterization and DNA-binding properties - Özçeşmeci, Mukaddes; Ecevit, Özgür Bülent; Sürgün, Serdar; Hamuryudan, Esin (Elsevier BV, 2013)
Abstract Selective replacement of the p-fluorine atom of 4-(2′,3′,4′,5′,6′-pentafluorobenzyloxy) phthalonitrile with N,N-dimethylaminoetanethiol gave 4-[2′,3′,5′,6′-tetrafluoro-4′-(2-dimethylaminoetanethio)benzyloxy]phthalonitrile. A peripherally tetra-substituted zinc(II) phthalocyanine was achieved by tetramerization of the new perfluorobenzyloxyphthalonitrile in the presence of zinc acetate. The zinc derivative was quaternized with methyl iodide to afford a water-soluble product. The new compounds were characterized by using elemental analyses, 1H NMR, 19F NMR, UV–vis and FT-IR spectroscopy and mass spectrometry. The interaction between the quaternized zinc phthalocyanine and calf thymus DNA was investigated in tris buffer (pH 7.4) by absorption and fluorescence spectroscopy. Upon addition of the quaternized zinc phthalocyanine, a change in the thermal denaturation profile of DNA was observed.